Pengaruh Sistemik Obat Tetes Mata. Pengaruh Tetes Mata Maleat Timolol Terhadap Tekanan Darah dan Detak Nadi Tanpa Beban: Penelidan Pendahuluan - Mu'tasimbillah Ghozi Mu'tasimbillah Ghozi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1989)
Timolol maleat, a new beta-adrenergic blocking agent, lowers intraocular pressure by decreasing actuous productiOri. It available in 0.25%;and 0.50% solution as an eye drop. The systemic effect of the timolol maleat 0.26% eye drops were observed among healthy medical students: The pulse rate and systolic blood pressure were insignificantly decreased but diastolic blood pressure was, insignificantly increased.Key Words: timolol maleat – beta-adrenergic blocking agents – blood pressure – pulse rate – intraocular pressure